1987
DOI: 10.1007/bf01852056
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of carrageenin-induced pedal oedema in rats by immobilisation stress

Abstract: The effect of immobilisation stress on acute pedal inflammation induced by carrageenin, and the mechanism of stress-induced anti-inflammatory effect, were investigated in male Wistar strain albino rats. Carrageenin-induced pedal inflammation oedema was attenuated by immobilisation stress in a time-dependent manner, when the rats were restrained for 30 min, 1 h, and 2 h immediately after the induction of the inflammation. Pentobarbitone exhibited significant anti-inflammatory effect of its own in an anaesthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Earlier reports have indicated that acute stress can inhibit plasma extravasation if the inflammatory challenge is presented during the stressful stimulus (10,11). However, the inhibition of plasma extravasation was transient and recovered soon after removal of the stressor.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Earlier reports have indicated that acute stress can inhibit plasma extravasation if the inflammatory challenge is presented during the stressful stimulus (10,11). However, the inhibition of plasma extravasation was transient and recovered soon after removal of the stressor.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, it seems unlikely that these transient actions would have noticeable effects on full-blown inflammatory disease, such as the aggravation of symptoms reported clinically (2-4). Transient inhibition of plasma extravasation during an acute stressor is mediated by the stress-activated sympathoadrenal axis (11) and may involve physiological changes (i.e., catechol-mediated increases in heart rate and blood pressure) that subside quickly after the stressor is removed.…”
Section: Discussionmentioning
confidence: 99%
“…The antistress activity was investigated by cold immobilization stress-induced gastric ulceration, after acute treatment in albino rats (Bhattacharya et al, 1987). Thus, rats were immobilized on wooden planks following the Freglys method of immobilization.…”
Section: Cold Immobilization Stress Induced Gastric Ulcersmentioning
confidence: 99%
“…The severity of ulcer was then calculated and the ulcer index was determined by adding the number of ulcers as reported earlier (Bhattacharya et al, 1987).…”
Section: Cold Immobilization Stress Induced Gastric Ulcersmentioning
confidence: 99%
“…The presence of a 17.00 peak, when carrageenan is used in this experiment, supports the idea that antigens efficacy is more prominent during the early activity span of mice and that the circadian rhythm observed is independant of the type of antigen. It has been suggested that the sympatho-medullary system is responsible for an antiinflammatory effect rather than the release of adrenal corticoids [11]. These findings indicate that inflammation inhibition is a consequence of increased central noradrenergic and peripheral sympathomeduUary activity.…”
mentioning
confidence: 97%